The New Testament : a historical introduction to the early Christian writings - Ehrman, Bart D (New York : Oxford University Press, 2000)
This new edition of Bart Ehrman's highly successful introduction approaches the New Testament from a consistently historical and comparative perspective, emphasizing the rich diversity of the earliest Christian literature. Rather than shying away from the critical problems presented by these books, Ehrman addresses the historical and literary challenges they pose and shows why scholars continue to argue over such significant issues as how the books of the New Testament came into being, what they mean, how they relate to contemporary Christian and non-Christian literature, and how they came to be collected into a canon of Scripture. Distinctive to this study is its emphasis on the historical, literary, and religious milieu of the Greco-Roman world, including early Judaism. As part of its historical orientation, this text also discusses works by other Christian writers who were roughly contemporary with the New Testament, such as the Gospel of Thomas, the Apocalypse of Peter, and the letters of Ignatius. This second edition features expanded coverage of the historical Jesus, adds new boxes on various topics (e.g., women in the New Testament and alternative approaches to the historical Jesus), incorporates a twelve-page color photo essay on illuminated manuscripts, and includes several important organizational changes. Ideal for undergraduate and seminary classes in the New Testament, Biblical Studies, and Christian Origins, The New Testament: A Historical Introduction to the Early Christian Writings, Second Edition, is an accessible, clearly written introduction that encourages students to consider the historical issues surrounding these writings. - Publisher
What is the New Testament? : the early Christians and their literature -- The world of early Christian traditions -- The traditions of Jesus in their Greco-Roman context -- The Christian gospels : a literary and historical introduction -- Jesus, the suffering son of God : the gospel according to Mark -- The synoptic problem and its significance for interpretation -- Jesus, the Jewish messiah : the gospel according to Matthew -- Jesus, the savior of the world : the gospel according to Luke -- Luke's second volume : the Acts of the apostles -- Jesus, the man sent from heaven : the gospel according to John -- From John's Jesus to the gnostic Christ : the Johannine epistles and beyond -- Jesus from different perspectives : other gospels in early Christianity -- The historical Jesus : sources, problems, and methods -- Excurus : the historian and the problem of miracle -- Jesus in context -- Jesus, the apocalyptic prophet -- From Jesus to the gospels -- Paul the apostle : the man and his mission -- Paul and his apostolic mission : 1 Thessalonians as a test case -- Paul and the crises of his churches : 1 and 2 Corinthians, Galatians, Philippians, and Philemon -- The gospel according to Paul : the letter to the Romans -- Does the tradition miscarry? : Paul in relation to Jesus, James, Thecla, and Theudas -- In the wake of the apostle : the Deutero-Pauline and pastoral Epistles -- From Paul's female colleagues to the pastor's intimidated women : the oppression of women in early Christianity -- Christians and Jews : Hebrews, Barnabas, and later anti-Jewish literature -- Christians and pagans : 1 Peter, the letter of Ignatius, the martyrdom of Polycarp, and later apologetic literature -- Christians and Christians : James, the Didache, Polycarp, 1 Clement, Jude, and 2 Peter -- Christians and the cosmos : the Revelation of John, the Shepherd of Hermas, and the Apocalypse of Peter
Includes bibliographical references and index
Keywords: Bible. -- Introductions; Einführung; Introductions